Preparation method of FeMn-based layered oxide positive electrode material of sodium-ion battery
By using solid phase sintering method to coat the zinc-based material on the surface of the iron-manganese-based layered oxide in the positive electrode material of sodium ion battery, the problems of low circulation performance and high residual alkali are solved, and high stability and excellentness are achieved cyclic performance.
Patent Information
- Application Number
- CN202411401767.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-07
AI Technical Summary
The existing sodium ion battery layered oxide positive electrode materials have low circulation performance and high residual alkali. The processing mixture is prone to jelly agglomeration, which hinders its commercial development.
采用简单的固相烧结法,将锌基材料包覆于铁锰基层状氧化物表面,通过煅烧和降温步骤制备包覆的铁锰基层状氧化物正极材料。
It effectively reduces the side reactions of the electrolyte during charging and discharging, improves the circulation performance of the battery, has high stability and good rate performance, and is suitable for commercial production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery. Background Art
[0002] Sodium-ion batteries are an important technical supplement to lithium-ion batteries because the distribution of lithium resources is limited and its abundance is far less than that of sodium, and the price of its main raw material, lithium carbonate, also restricts it. Sodium-ion batteries are relatively low in cost and are suitable as a supplement to lithium-ion batteries for use in energy storage, small cars and other scenarios. Among them, the positive electrode material of sodium-ion batteries will greatly affect the overall performance of the battery. At present, layered oxide materials have become the mainstream positive electrode materials in the market due to their simple synthesis methods and excellent electrical properties. However, due to its low cycle performance, high residual alkali, and easy jelly agglomeration during processing, its commercial development has been hindered. Currently, commonly used modification methods include element doping, material coating, structural design, etc., but the operation process is usually more complicated, difficult, and costly. While improving stability, it may cause capacity loss and cause new problems. Therefore, it is urgent to find a simple multi-performance modification method. Summary of the invention
[0003] In view of the above shortcomings of the prior art, the present invention provides a method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery. Through a simple solid-phase sintering method, a zinc-based material is used to coat and modify the iron-manganese-based layered oxide, which effectively reduces the side reactions of the electrolyte during the charge and discharge process and improves the cycle performance of the battery.
[0004] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0005] A method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery comprises the following steps: uniformly mixing an iron-manganese-based layered oxide with a coating, calcining, and cooling to obtain a coated iron-manganese-based layered oxide positive electrode material; the coating is selected from a mixture of one or more of zinc oxide, zinc carbonate, zinc acetate, zinc nitrate, zinc sulfate, and zinc phosphate.
[0006] Furthermore, the coating is zinc oxide.
[0007] Furthermore, the particle size of the coating is 0.1-20 μm.
[0008] Furthermore, the particle size of the coating is below 2 μm, accounting for 10-50%, the particle size is 2-5 μm, accounting for 10%-50%, the particle size is 5-12 μm, accounting for 0-30%, and the particle size is 12-20 μm, accounting for 0-10%. By performing particle size distribution processing on the coating, the coating effect can be improved and the coating can be made more complete.
[0009] Furthermore, the iron-manganese-based layered oxide contains Fe, Mn and other doped metal elements, and the chemical formula is Na X Fe a Mn b TM c O2, wherein 0.6≤X≤1.05, a+b+c=1, and TM includes but is not limited to one or more of Ni, Zn, Cu, Zn, Ti, Mg, Al, Co, K, Ca, and Li elements.
[0010] Furthermore, the mass ratio of the coating to the iron-manganese based layered oxide is (0.01-0.08):1.
[0011] Furthermore, the mass ratio of the coating to the iron-manganese based layered oxide is 0.03:1.
[0012] Furthermore, the calcination is carried out in an air atmosphere, including a one-step calcination or a two-step calcination.
[0013] Furthermore, the heating rate of the one-step calcination is 1-5°C / min, the calcination temperature is 400-650°C, and the calcination time is 3-10 h.
[0014] Furthermore, the heating rate of the two-step calcination is 1-5°C / min, the first stage calcination temperature is 300-500°C, the first stage calcination time is 3-6 h, the second stage calcination temperature is 800-950°C, and the second stage calcination time is 3-6 h.
[0015] The present invention also provides a sodium ion battery FeMn-based layered oxide positive electrode material prepared by the method.
[0016] Compared with the prior art, the present invention is beneficial in that:
[0017] (1) The present invention adopts a simple solid phase sintering method to coat the zinc-based material on the surface of the iron-manganese-based layered oxide, and the prepared coated iron-manganese-based layered oxide positive electrode material has the advantages of high stability, good rate performance and excellent cycle performance.
[0018] (2) The present invention further improves the coating effect by performing a particle size distribution treatment on the coating material, thereby achieving complete coating and further significantly improving the cycle performance of the iron-manganese-based layered oxide positive electrode material.
[0019] (3) The method of the present invention has a wide range of applications. The iron-manganese-based layered oxides include a variety of iron-manganese-based layered oxides including P2, O3 and P2 / O3 mixed phases. The coated iron-manganese-based layered oxide positive electrode material prepared by the method of the present invention can effectively improve the comprehensive electrochemical performance while reducing side reactions with the electrolyte.
[0020] (4) The method of the present invention is simple to operate, low in cost, and is conducive to commercial-scale production. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The invention provides a method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery, comprising the following steps: uniformly mixing an iron-manganese-based layered oxide with a coating, calcining, and cooling to obtain a coated iron-manganese-based layered oxide positive electrode material; the coating is selected from a mixture of one or more of zinc oxide, zinc carbonate, zinc acetate, zinc nitrate, zinc sulfate, and zinc phosphate.
[0023] In some examples, the particle size of the coating is 0.1-20 μm.
[0024] In some examples, the particle size of the coating is 10-50% below 2 μm, the particle size is 2-5 μm, the particle size is 10%-50%, the particle size is 5-12 μm, the particle size is 0-30%, and the particle size is 12-20 μm, the particle size is 0-10%.
[0025] In some examples, the iron-manganese-based layered oxide contains Fe, Mn and other doping metal elements, and the chemical formula is Na X Fe a Mn b TM c O2, wherein 0.6≤X≤1.05, a+b+c=1, and TM includes but is not limited to one or more of Ni, Zn, Cu, Zn, Ti, Mg, Al, Co, K, Ca, and Li elements.
[0026] The iron-manganese-based layered oxide can be the iron-manganese-based layered oxide (product number: LM-1A) developed by our company, or it can be the iron-manganese-based layered oxide obtained by high-temperature calcination of common precursors on the market (such as NiFeMn111, 424, etc.) and a sodium source; the phase type of the iron-manganese-based layered oxide can include one of P2 type, P2 / O3 type, and O3 type.
[0027] In the following specific embodiments, unless otherwise specified, the iron-manganese-based layered oxide is an iron-manganese-based layered oxide (product number: LM-1A) developed by our company.
[0028] In some examples, the mass ratio of the coating to the iron-manganese-based layered oxide is (0.01-0.08):1.
[0029] In some examples, the calcination is performed under an air atmosphere, including a one-step calcination or a two-step calcination.
[0030] In some examples, the one-step calcination has a heating rate of 1-5°C / min, a calcination temperature of 400-650°C, and a calcination time of 3-10 h.
[0031] In some examples, the two-step calcination has a heating rate of 1-5°C / min, a first-stage calcination temperature of 300-500°C, a first-stage calcination time of 3-6 h, a second-stage calcination temperature of 800-950°C, and a second-stage calcination time of 3-6 h.
[0032] In the following specific embodiments, unless otherwise specified, the particle size of the coating is 40% below 2 μm, 40% is 2-5 μm, 10% is 5-12 μm, and 10% is 12-20 μm.
[0033] Example 1
[0034] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0035] P2 type iron-manganese based layered oxide and zinc oxide were mixed evenly in a ball mill at a mass ratio of 1: 0.03, and the fully mixed powder was placed in a box furnace for calcination at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h. The material was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance was tested. The sample was recorded as sample A1. The electrochemical performance test results are shown in Table 1.
[0036] Example 2
[0037] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0038] The P2 type iron-manganese based layered oxide and zinc oxide were mixed uniformly in a ball mill at a mass ratio of 1: 0.03, and the fully mixed powder was placed in a box furnace for calcination at a heating rate of 5 ℃ / min, the first stage calcination temperature was 400 ℃, the first stage calcination time was 4 h, the second stage calcination temperature was 800 ℃, the second stage calcination time was 4 h, and then cooled to room temperature to obtain the coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material, which was assembled with metallic sodium into a button cell for electrochemical performance test, recorded as sample A2, and the electrochemical performance test results are shown in Table 1.
[0039] Example 3
[0040] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0041] The P2 type iron-manganese based layered oxide and zinc oxide were mixed uniformly in a ball mill at a mass ratio of 1: 0.01, and the fully mixed powder was placed in a box furnace for calcination at a heating rate of 5 °C / min, a calcination temperature of 600 °C, and a calcination time of 6 h. The powder was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance was tested. The sample was recorded as sample A3. The electrochemical performance test results are shown in Table 1.
[0042] Example 4
[0043] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0044] The P2 type iron-manganese based layered oxide and zinc oxide were mixed evenly in a ball mill at a mass ratio of 1: 0.05, and the fully mixed powder was placed in a box furnace for calcination at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h. The powder was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance test was performed. The sample was recorded as sample A4. The electrochemical performance test results are shown in Table 1.
[0045] Example 5
[0046] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0047] The P2 type iron-manganese based layered oxide and zinc sulfate were mixed uniformly in a ball mill at a mass ratio of 1: 0.03, and the fully mixed powder was placed in a box furnace for calcination at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h. The powder was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance was tested. The sample was recorded as sample A5. The electrochemical performance test results are shown in Table 1.
[0048] Example 6
[0049] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0050] P2 type iron-manganese based layered oxide, zinc sulfate and zinc acetate were mixed evenly in a ball mill at a mass ratio of 1: 0.015: 0.015, and the fully mixed powder was placed in a box furnace for calcination at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h. The material was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and subjected to an electrochemical performance test. The sample was recorded as sample A6. The electrochemical performance test results are shown in Table 1.
[0051] Example 7
[0052] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0053] P2 type iron-manganese based layered oxide and zinc oxide (particle size of 10-20 μm) were mixed uniformly in a ball mill at a mass ratio of 1: 0.03. The fully mixed powder was placed in a box furnace and calcined at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h. The powder was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance was tested. The sample was recorded as sample A7. The electrochemical performance test results are shown in Table 1.
[0054] Example 8
[0055] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0056] The O3 type iron-manganese based layered oxide and zinc oxide were uniformly mixed in a ball mill at a mass ratio of 1: 0.03. The fully mixed powder was placed in a box furnace and calcined at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h. The powder was then cooled to room temperature to obtain a coated O3 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance was tested. The sample was recorded as sample A8. The electrochemical performance test results are shown in Table 1.
[0057] Comparative Example 1
[0058] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0059] The P2 type iron-manganese based layered oxide and zirconium oxide were mixed evenly in a ball mill at a mass ratio of 1: 0.03. The fully mixed powder was placed in a box furnace and calcined at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h. The powder was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance was tested. The sample was recorded as sample B1. The electrochemical performance test results are shown in Table 1.
[0060] Comparative Example 2
[0061] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0062] The P2 type iron-manganese based layered oxide and alumina were mixed uniformly in a ball mill at a mass ratio of 1: 0.03. The fully mixed powder was placed in a box furnace and calcined at a heating rate of 5 °C / min, a calcination temperature of 600 °C, and a calcination time of 6 h. The powder was then cooled to room temperature to obtain a coated P2 type sodium ion battery iron-manganese based layered oxide positive electrode material. The material was assembled into a button cell with metallic sodium and the electrochemical performance was tested. The sample was recorded as sample B2. The electrochemical performance test results are shown in Table 1.
[0063] Comparative Example 3
[0064] A sodium ion battery FeMn-based layered oxide positive electrode material, the preparation steps are as follows:
[0065] According to the stoichiometric ratio of the iron-manganese based layered oxide (product number: LM-1A) developed by our company, raw materials such as sodium, iron, and manganese are mixed, and then 3% of the total mass of the raw materials is added with zinc oxide; the above materials are mixed evenly in a ball mill, and the fully mixed powder is placed in a box furnace for calcination at a heating rate of 5 ℃ / min, a calcination temperature of 600 ℃, and a calcination time of 6 h, and then cooled to room temperature to obtain a sodium ion battery iron-manganese based layered oxide positive electrode material, which is assembled with metallic sodium into a button cell for electrochemical performance testing, recorded as sample B3, and the electrochemical performance test results are shown in Table 1.
[0066] Sample 1: A button cell was assembled with P2 type iron-manganese based layered oxide and metallic sodium, and the electrochemical performance test was carried out. The electrochemical performance test results are shown in Table 1.
[0067] Sample 2: A button cell was assembled with O3 type iron-manganese based layered oxide and metallic sodium, and the electrochemical performance test was carried out. The electrochemical performance test results are shown in Table 1.
[0068] Table 1: Electrochemical performance test results
[0069]
[0070] From the data in Table 1, it can be seen that after coating, the residual alkali is physically wrapped by zinc oxide, the pH value decreases significantly, and the cycle performance is improved, among which sample A1 is the most excellent. The 0.1 C charge capacity, discharge capacity and discharge capacity at 1 C rate in sample A1 are consistent with those of sample 1, while the cycle retention rate at 1 C rate of 100 cycles is increased by 7.7% compared with sample 1, and the pH is reduced by 0.21, indicating that the coating has a significant effect, the cycle stability is significantly improved, and the balance between physical coating and active mass reduction is achieved, reducing the side reaction between the positive electrode material and the electrolyte. Comparing the electrochemical performance data of sample A8 and sample 2, it can be seen that the 0.1 C charge capacity, discharge capacity and discharge capacity at 1 C rate of sample A8 are lower than those of sample 2, but the cycle retention rate at 1 C rate of sample A8 is increased by 10.1%, which also shows that the coating has a significant effect on the cycle performance of the iron-manganese-based layered oxide positive electrode material. At the same time, the pH value is also significantly reduced, which is beneficial to the subsequent processing of the battery. The coating amount of zinc oxide in sample A3 is 1%, and the pH has decreased. Its charge-discharge specific capacity is not much different from that of sample 1, and the 1 C cycle performance has also improved less, indicating that the coating amount of 1% is small. Although it has a certain effect on reducing residual alkali, it fails to effectively inhibit side reactions. The coating amount of zinc oxide in sample A4 is 5%. Although its 100-cycle cycle retention rate at 1 C rate is improved compared with sample 1, the 0.1 C charge and discharge specific capacity has decreased significantly. This is because the introduction of zinc oxide reduces the mass of the overall active material, thereby reducing the capacity. The zinc oxide in sample A7 is zinc oxide that has not been treated with particle size distribution. Compared with sample 1, its coating is effective, but the relative improvement is small, mainly because the average particle size of zinc oxide that has not been treated with particle size distribution is too large, resulting in incomplete coating. B1 and B2 are sintered and coated with zirconium oxide and aluminum oxide, which has a greater impact on the battery capacity, and the cycle stability is not significantly improved. It is better to use the zinc-based material coating described in the present invention. B3 uses zinc-based materials to directly sinter with various raw materials of iron-manganese-based layered oxides according to the final formula ratio to form a bulk material. Its performance is far inferior to the method of the present invention, which is based on iron-manganese-based layered oxides and only coats the zinc-based material on the surface through one / two sinterings.
[0071] In summary, the present invention adopts a simple solid-phase sintering method to coat the zinc-based material on the surface of the iron-manganese-based layered oxide, and the prepared coated iron-manganese-based layered oxide positive electrode material has the advantages of high stability, good rate performance and excellent cycle performance. In addition, the method of the present invention is simple to operate, low in cost, and is conducive to commercial-scale production.
[0072] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery, characterized in that: The method comprises the following steps: uniformly mixing an iron-manganese-based layered oxide and a coating, calcining, and cooling to obtain a coated iron-manganese-based layered oxide positive electrode material; the coating is selected from a mixture of one or more of zinc oxide, zinc carbonate, zinc acetate, zinc nitrate, zinc sulfate, and zinc phosphate.
2. The method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery according to claim 1, characterized in that: The coating is zinc oxide.
3. The method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery according to claim 1, characterized in that: The particle size of the coating is 0.1-20 μm.
4. The method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery according to claim 3, characterized in that: The particle size of the coating is 10-50% below 2 μm, 10%-50% of the particle size is 2-5 μm, 0%-30% of the particle size is 5-12 μm, and 0%-10% of the particle size is 12-20 μm.
5. The method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery according to claim 1, characterized in that: The chemical formula of the iron-manganese based layered oxide is Na X Fe a Mn b TM c O2, wherein 0.6≤X≤1.05, a+b+c=1, and TM includes but is not limited to one or more of Ni, Zn, Cu, Zn, Ti, Mg, Al, Co, K, Ca, and Li elements.
6. The method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery according to claim 1, characterized in that: The mass ratio of the coating to the iron-manganese based layered oxide is (0.01~0.08):
1.
7. The method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery according to claim 6, characterized in that: The mass ratio of the coating to the iron-manganese-based layered oxide is 0.03:
1.
8. The method for preparing a FeMn-based layered oxide positive electrode material for a sodium ion battery according to claim 1, characterized in that: The calcination is carried out in an air atmosphere, including one-step calcination or two-step calcination; wherein the heating rate of the one-step calcination is 1-5°C / min, the calcination temperature is 400-650°C, and the calcination time is 3-10 h; the heating rate of the two-step calcination is 1-5°C / min, the first stage calcination temperature is 300-500°C, the first stage calcination time is 3-6 h, the second stage calcination temperature is 800-950°C, and the second stage calcination time is 3-6 h.
9. A FeMn-based layered oxide positive electrode material for a sodium ion battery prepared by the method according to any one of claims 1 to 8.